2008
DOI: 10.2152/jmi.55.133
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of estradiol and progesterone on the oxidative stress-induced production of chemokine and proinflammatory cytokines in murine peritoneal macrophages

Abstract: In inflammatory and oxidative liver injury, virus proteins and reactive oxygen species are involved in the regulation of proinflammatory cytokine production by macrophages. This study investigated the effects of estradiol (E2) and progesterone on the unstimulated and oxidative stress-stimulated production of tumor necrosis factor (TNF)-alpha, interleukin (IL)-1beta, macrophage inflammatory protein (MIP)-2, and macrophage chemotactic protein (MCP)-1 by peritoneal macrophages isolated from male and female mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…[55] In addition, E 2 inhibited the production of TNF-a by the unstimulated and hydrogen peroxide-stimulated macrophages from males and females. [56] Parallel to these findings, the present data demonstrate that elevated serum TNF-a levels of CRF rats are depressed by exogenous E 2 treatment, suggesting that E 2 -induced alleviation of CRF-induced oxidative damage involves the modulation of the synthesis of TNF-a.…”
Section: Discussionsupporting
confidence: 82%
“…[55] In addition, E 2 inhibited the production of TNF-a by the unstimulated and hydrogen peroxide-stimulated macrophages from males and females. [56] Parallel to these findings, the present data demonstrate that elevated serum TNF-a levels of CRF rats are depressed by exogenous E 2 treatment, suggesting that E 2 -induced alleviation of CRF-induced oxidative damage involves the modulation of the synthesis of TNF-a.…”
Section: Discussionsupporting
confidence: 82%
“…4). It has been reported that estrogen attenuates the expressions of TNFα and MCP-1via the estrogen receptor in female mice (Huang et al, 2008). Thus, these results indicated that TAM would exert a hepatoprotective effect against inflammation in the steatosis and NASH model mice.…”
mentioning
confidence: 63%
“…Progesterone, meanwhile, was shown to limit the production of NO by LPSactivated alveolar macrophages [34] and bone marrow-derived macrophages (BMDM) activated with a combination of interferon (IFN)-␥ and LPS [35]. It also stimulated the secretion of TNF-␣, IL-1␤ and the chemokine macrophage inflammatory protein (MIP)-2 from unactivated peritoneal macrophages [36] while estradiol suppressed the production of these three inflammatory mediators [36]. In a mouse macrophage cell line, estradiol blocked LPS's induction of its own receptor (TLR4), and attenuated cell activation, as assessed morphologically [37].…”
Section: Macrophagesmentioning
confidence: 99%